Determinants of Mother's Financial Literacy on Family Economic Welfare: Maqashid Sharia Analysis - Siti Nur Azizah; Annisa Nur Salam (Journal Research of Social Science, Economics, and Management, 2021)
This study involved determinants of maternal financial literacy on household welfare from the perspective of maqashid al-syariah. This study used two waves of IFLS, namely IFLS-4 (2007) and IFLS-5 (2014). In addition, several data related to the value of household assets and household characteristics are available based on IFLS-4 (2007). The study uses a quantitative approach with descriptive analysis and regression using the Ordinary Least Square (OLS) method. The findings in this study include the expenditure variable has no significant effect on the family welfare variable. The social consumption variable has a negative and significant impact on family welfare. The savings variable has a positive and significant effect on family welfare. The variable was to borrow funds has a positive and significant effect on family welfare. The pension fund variable has a positive and significant effect on family welfare. Mother's education variable has a negative and significant effect on family welfare. The variable number of family members has a positive and significant effect on the family's economic interest. The variables of residence and year have no significant impact on the family's economic welfare.